2012
DOI: 10.1542/peds.2012-0334
|View full text |Cite
|
Sign up to set email alerts
|

Parents Smoking in Their Cars With Children Present

Abstract: WHAT'S KNOWN ON THIS SUBJECT: Tobacco smoke exposure is associated with increased morbidity in children, and exposure in cars can be particularly intense. The American Academy of Pediatrics policy statement recommends that pediatricians assist families in adopting smoke-free car policies. WHAT THIS STUDY ADDS:In this study, few smoking parents had a strictly enforced smoke-free car policy. Low rates of pediatric health care providers addressing smoking in the car highlights the need for improved pediatric inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 36 publications
0
30
0
6
Order By: Relevance
“…Counseling by the pediatrician or other clinicians should encourage the family to make the home and car smoke-free. 108 Smoking in a motor vehicle exposes children to high concentrations of tobacco smoke. 109 Although smoke-free policies can reduce a child's tobacco smoke exposure, 110 they are unlikely to eliminate it as long as close family members and/or caregivers smoke.…”
Section: Treatment Of Tobacco Use In Parentsmentioning
confidence: 99%
“…Counseling by the pediatrician or other clinicians should encourage the family to make the home and car smoke-free. 108 Smoking in a motor vehicle exposes children to high concentrations of tobacco smoke. 109 Although smoke-free policies can reduce a child's tobacco smoke exposure, 110 they are unlikely to eliminate it as long as close family members and/or caregivers smoke.…”
Section: Treatment Of Tobacco Use In Parentsmentioning
confidence: 99%
“…This finding was unexpected as previous survey results indicate that in comparison with older children, adolescents, and adults, younger children are less likely to be exposed to household and vehicular SHS (Hawkins & Berkman, 2011;Max, Sung, & Shi, 2012;Nabi-Burza et al, 2012). Previous studies using biological markers of SHSe have reported that youngsters who are exposed to SHS may be exposed to higher concentrations than their older peers (Butz et al, 2011;Groner et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…10,[12][13][14][15][16][17] In brief, all parents of children making any type of visit were approached immediately after the visit by an RA and asked to be interviewed. Those who spoke English, had smoked a cigarette (even a puff) within the past 7 days, were aged 18 years or older, and would have a contact number to be reached over the next year were eligible for enrollment.…”
Section: Methodsmentioning
confidence: 99%